THE INFLUENCE OF PROMOTION AND QUALITY SERVICES ON PURCHASING DECISION FOR ELECTRONIC TRANSACTION SERVICE AT ALFAMIDI KUTABUMI - Agung Tri Putranto (Yayasan Education and Social Center, 2021)
The title of this research is “the impact of promotion and quality services on purchasing decision for electronic transaction service at alfamidi kutabumi”. this study aims to determine the significance of the effect of promotion and service quality partially and simultaneously on electronic transaction decisions at Alfamidi Kutabumi. This study uses quantitative methods, the number of populations is not known for sure so that based on the Rao Purba formula, the number of samples is 96.4 and is rounded up to 100 respondents by the researcher. Technical analysis of instrument test data (validity test, reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test), hypothesis testing (t-test, F test). From the results of the research, the X 1 variable has a significant effect on the Y variable with the regression equation Y = 9.450 + 0.230 X 1, the correlation value of 0.579 means that the two variables have a moderate level of relationship with a coefficient of determination of 33.5%. Hypothesis test obtained t arithmetic > t table or (7.033 > 1.984). Thus H 0 is rejected and H 1 accepted. Variable X 2 has a significant effect on variable Y with the regression equation Y = 9.294 + 0.375 X 2, the correlation value is 0.570, meaning that both have a moderate level of relationship with a coefficient of determination of 32.4%. Hypothesis test obtained t count > t table or (6.859 > 1.984). Variables X 1 and X 2 simultaneously have a significant effect on variable Y with the regression equation Y = 4.407 + 0.158X 1 + 0.249X 2 . The correlation value of 0.667 means that the independent variable and the dependent variable have a strong relationship with a coefficient of determination of 44.5% while the remaining 55.5% is influenced by other factors. Hypothesis test obtained value of F arithmetic > F table or (38.891 > 2,700). Thus H 0 is rejected and H 3 is accepted